Pengaruh Kualitas Produk Dan Lokasi Terhadap Keputusan Pembelian Pada Mie Ayam Pedas Sugih Di Gegerkalong Kota Bandung - Dini Lestari; Maddinsyah, Ali (SM Institute, 2025)
This study aims to determine and analyse the quality of products and location on the purchasing decisions of Sugih mie ayam pedas sugih in Gegerkalong, Bandung City. The method used in this study is a descriptive-verificative method with a quantitative approach. The data analysis technique used is descriptive-verificative. In the context of this study, the population consists of all consumers who eat at locations in Gegerkalong, Bandung City. The sampling technique used in this study is non-probability sampling with a purposive sampling approach involving 100 consumers. The analysis method used is linear regression analysis with hypothesis testing, namely the t-test (partial) and the f-test (simultaneous). Based on the results of this study, it shows that product quality (X1) has a significant effect on purchasing decisions, as evidenced by a t-value of 3.381 > t-table 1.66 and a significance value of 0.001 < 0.05. Location (X2) was also proven to have a significant effect on purchasing decisions partially with a t-value of 4.082 > t-table 1.66 and a significance value of 0.000 < 0.05. Concurrently, both independent variables, namely product quality and location, have a significant influence on purchasing decisions, as indicated by the calculated f value of 15.330 > f table 3.939 and a significance value of 0.000 < 0.05. Therefore, the regression model used is declared valid.